Association of Maternal Serum Retinol-Binding Protein Levels with Adverse Pregnancy Outcomes: A Retrospective Cohort Study - Dong, Wenjing; Chu, Xuelian; Wang, Yanan; Gu, Linyuan; Chen, Yiming (American Journal of Perinatology, 2025)
This study aimed to determine the correlation between decreased or increased retinol-binding protein (RBP) levels during pregnancy and adverse pregnancy outcomes.A retrospective cohort study was conducted to analyze the data of 16,094 pregnant women who participated in serum RBP level detection during pregnancy. The chi-square test or Mann–Whitney U test was used for the univariate analysis of qualitative or quantitative data. Multiple logistic regression analysis, odds ratio (OR), and 95% confidence interval were used to evaluate the effect of RBP levels on adverse pregnancy outcomes.The groups showed a significant difference in RBP levels (p < 0.001). The results of multiple logistic regression analysis revealed that twins (OR = 2.631), upper respiratory tract infection (URTI, OR = 2.596), premature delivery (OR = 1.833), and macrosomia (OR = 1.524) were correlated with low retinol-binding protein (L-RBP), while preeclampsia (PE, OR = 0.147), intrahepatic cholestasis of pregnancy (OR = 1.654), gestational hypertension (GH, OR = 1.646), oligohydramnios (OR = 1.487), and advanced maternal age (OR = 1.470) were correlated with high retinol-binding protein (H-RBP). Decreased or increased RBP levels were correlated with hyperlipidemia (OR = 1.738, 2.857), Antenatal anemia (OR = 1.378, 0.791), gestational diabetes mellitus (GDM, OR = 1.272, 0.796), and small infant size (OR = 0.664, 1.444). L-RBP may indicate an increased risk of antenatal anemia and GDM, whereas H-RBP may indicate a decreased risk of antenatal anemia and GDM. Pregnant women with H-RBP were more likely to give birth to smaller infants, whereas those with L-RBP had a lower risk of this outcome. Additionally, mothers with H-RBP were not likely to give birth to male infants.Hyperlipidemia, URTI, GH, PE, and GDM affect serum RBP levels, and these exposure factors can lead to different degrees of adverse pregnancy outcomes.
Keywords: maternal serum; retinol-binding protein; adverse pregnancy outcomes; retrospective cohort study; odds ratio